james and the giant peach - Dahl, Roald; Roald Dahl (New York Penguin Group, Inc., 1961)
When james accidentally drop some magic crystals by the old peach tree, strange things start to happen. The peach at the top of the three begins to grow, and before long it's big as a house. Then james discovers a secret entranceway into the fruit, and when he crawls inside, he meets a bunch of oversized friends-grasshopper, centipede, ladybug, and more. After years of feeling like an outsider in his aunt's house, james has finally found a place where he belongs. With a snip of the stem, the peach starts rolling away, and the adventure begins!
English